KECENDERUNGAN ISU DEMONSTRASI PADA PEMBERITAAN HARIAN FAJAR PERIODE 2017 (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2019)
This research uses a content analysis to know the tendency of demonstration news issue that publish by Fajar. Sample is taken by the demonstrations occurred in South Sulawesi for the period of 2017. This research method uses a quantitative approach then explain it more detail.This research method shows that Fajar is selective to present demonstration news especially related with public interest. The land dispute and infrastructure development are the most dominant issues for demonstration news. In the city,  the issue tends to land dispute while the issue in the rural tends to infrastructure development. For news placement, Fajar is flexible to lay the demonstration events. Keywords: content analysis, news, demonstration news